Interplay of Self-Efficacy Beliefs and Teaching Competencies in Science: A Quantitative Inquiry Through the Lens of Science Teachers - Dr. Farah Deeba; Dr. Iqbal Ahmad; Aisha Nargis (Research Journal of Psychology, 2024)
Science teachers’ self-efficacy towards teaching of science play a vital role to enhance their teaching competencies in this subject. The present study was carried out to investigate interplay of science teachers’ self-efficacy beliefs and their teaching competencies in subject of Science. The study adopted a descriptive survey research design in which 444 subject specialists of Science teaching in 213 High Schools of District Multan were the population of the study. Questionnaire was administered over all teachers by using Census method out of which total 395 responded to the study scale. The study used two Likert type scales to measure the studied variables; self-efficacy beliefs and teaching competencies in Science. The overall combined reliability of the two scales was (r=.934).To analyze the data, both Descriptive and Inferential statistics were used. Under Descriptive statistics, frequency, percentage, Mean Score and Standard Deviation were counted and Pearson’s r was used for correlational analysis as inferential statistics. Study results showed that majority of respondents (science teachers) believed that they possess high self-efficacy and also have good teaching competence in their science teaching. Study results also indicated that the teachers have very high levels of self-efficacy beliefs and moderate level of teaching competence in science teaching. The study found a strong, significant and positive interplay between self-efficacy and teaching competence in Science. Gender based interplay between the variables was also found strong. The study recommended that continuous professional workshops be conducted for the teachers in which they may learn motivational techniques for their students as in their view even with good teaching skills due to demotivation students they feel themselves unable to motivate students to learn science and enhance their interest for science.